Room‐Temperature Phosphorescence in Metal‐Free Organic Materials. Issue 7 (2nd April 2019) - Ma, Huili; Lv, Anqi; Fu, Lishun; Wang, Shan; An, Zhongfu; Shi, Huifang; Huang, Wei
Abstract: Purely organic materials with room‐temperature phosphorescence (RTP) have attracted a growing interest for their potential applications in biological imaging, digital encryption, optoelectronic devices, and so on. To date, many strategies have succeeded in designing efficient organic RTP materials by overcoming the spin‐forbidden transition between singlet and triplet states. However, the underlying mechanisms of RTP still remain ambiguous. Such spin prohibition in phosphorescence are clarified, herein, from the perspective of perturbation theory, helping to understand the intrinsic relationship among various phosphorescence parameters, like phosphorescence efficiency, lifetime, intersystem crossing rate, as well as radiative and nonradiative rates. Taking into consideration the recent progress in organic RTP materials, these factors are further illustrated by a selection of the most relevant molecules. In addition, some novel RTP phenomena are also reviewed, thus providing an excellent guideline to constructing efficient RTP materials. Abstract : Phosphorescence is a radiative transition from the triplet excited state, which is populated from the excited singlet state through intersystem crossing. Theoretical understanding on this spin‐forbidden transition are ambiguous for organic room‐temperature phosphorescence (RTP) materials. Recent viewpoints on organic RTP materials are clarified herein, which is favorable to exploring the intrinsic RTP mechanism and designing efficient phosphorescence materials.